2009
DOI: 10.1099/mic.0.027623-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel carotenoid 1,2-hydratase (CruF) from two species of the non-photosynthetic bacterium Deinococcus

Abstract: A novel carotenoid 1,2-hydratase (CruF) responsible for the C-19,29 hydration of c-carotene was identified in the non-photosynthetic bacteria Deinococcus radiodurans R1 and Deinococcus geothermalis DSM 11300. Gene expression and disruption experiments demonstrated that dr0091 and dgeo2309 encode CruF in D. radiodurans and D. geothermalis, respectively. Their homologues were also found in the genomes of cyanobacteria, and exhibited little homology to the hydroxyneurosporene synthase (CrtC) proteins found mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Genes involved in carotenoid biogenesis have been shown to confer a modest level of radiation resistance by scavenging electrons from ROSs [35]. D. gobiensis produces carotenoids, and the carotenoid biosynthetic pathway is similar to that found in D. radiodurans [36]. In addition, we observed that genes for secondary metabolite biosynthesis of carotenoids, vitamin B1, vitamin B12, NAD + and cytochrome P450 were strongly downregulated after UV irradiation.…”
Section: Resultssupporting
confidence: 61%
“…Genes involved in carotenoid biogenesis have been shown to confer a modest level of radiation resistance by scavenging electrons from ROSs [35]. D. gobiensis produces carotenoids, and the carotenoid biosynthetic pathway is similar to that found in D. radiodurans [36]. In addition, we observed that genes for secondary metabolite biosynthesis of carotenoids, vitamin B1, vitamin B12, NAD + and cytochrome P450 were strongly downregulated after UV irradiation.…”
Section: Resultssupporting
confidence: 61%
“…strain PCC 7002 (Cyanobacteria) (Graham & Bryant, 2009) and for deinoxanthin in Deinococcus radiodurans (Deinococcus-Thermus) (Sun et al, 2009). The functions of carotenoid 3,4-desaturase have been confirmed: CrtD in purple photosynthetic bacteria (Takaichi, 2009), for myxol in the marine bacterium strain P99-3 (Bacteroidetes) (Teramoto et al, 2004) and for deinoxanthin in D. radiodurans (Tian et al, 2008).…”
Section: S Takaichi and Othersmentioning
confidence: 78%
“…6. Both deinoxanthin and flexixanthin are believed to be synthesised from lycopene [41,42], but deinoxanthin differs by an additional hydroxyl functional group on the C2 carbon of the β-ring [43]. In contrast to deinoxanthin, β-carotene is a very widespread pigment, and is the dominant carotenoid in Synechocystis cyanobacteria.…”
Section: Discussionmentioning
confidence: 95%